Endoscopic tissue sampling – Part 2: Lower gastrointestinal tract. European Society of Gastrointestinal Endoscopy (ESGE) Guideline - Pouw, Roos E.; Bisschops, Raf; Gecse, Krisztina B.; de Hertogh, Gert; Iacucci, Marietta; Rutter, Matthew; Barret, Maximilien; Biermann, Katharina; Czakó, László; Hucl, Tomas; Jansen, Marnix; Savarino, Edoardo; Spaander, Manon C. W.; Schmidt, Peter T.; Dinis-Ribeiro, Mário; Vieth, Michael; van Hooft, Jeanin E. (Endoscopy, 2021)
1 ESGE suggests performing segmental biopsies (at least two from each segment), which should be placed in different specimen containers (ileum, cecum, ascending, transverse, descending, and sigmoid colon, and rectum) in patients with clinical and endoscopic signs of colitis.Weak recommendation, low quality of evidence.2 ESGE recommends taking two biopsies from the right hemicolon (ascending and transverse colon) and, in a separate container, two biopsies from the left hemicolon (descending and sigmoid colon) when microscopic colitis is suspected.Strong recommendation, low quality of evidence.3 ESGE recommends pancolonic dye-based chromoendoscopy or virtual chromoendoscopy with targeted biopsies of any visible lesions during surveillance endoscopy in patients with inflammatory bowel disease. Strong recommendation, moderate quality of evidence.4 ESGE suggests that, in high risk patients with a history of colonic neoplasia, tubular-appearing colon, strictures, ongoing therapy-refractory inflammation, or primary sclerosing cholangitis, chromoendoscopy with targeted biopsies can be combined with four-quadrant non-targeted biopsies every 10 cm along the colon. Weak recommendation, low quality of evidence.5 ESGE recommends that, if pouch surveillance for dysplasia is performed, visible abnormalities should be biopsied, with at least two biopsies systematically taken from each of the afferent ileal loop, the efferent blind loop, the pouch, and the anorectal cuff.Strong recommendation, low quality of evidence.6 ESGE recommends that, in patients with known ulcerative colitis and endoscopic signs of inflammation, at least two biopsies be obtained from the worst affected areas for the assessment of activity or the presence of cytomegalovirus; for those with no evident endoscopic signs of inflammation, advanced imaging technologies may be useful in identifying areas for targeted biopsies to assess histologic remission if this would have therapeutic consequences. Strong recommendation, low quality of evidence.7 ESGE suggests not biopsying endoscopically visible inflammation or normal-appearing mucosa to assess disease activity in known Crohn’s disease.Weak recommendation, low quality of evidence.8 ESGE recommends that adequately assessed colorectal polyps that are judged to be premalignant should be fully excised rather than biopsied.Strong recommendation, low quality of evidence.9 ESGE recommends that, where endoscopically feasible, potentially malignant colorectal polyps should be excised en bloc rather than being biopsied. If the endoscopist cannot confidently perform en bloc excision at that time, careful representative images (rather than biopsies) should be taken of the potential focus of cancer, and the patient should be rescheduled or referred to an expert center.Strong recommendation, low quality of evidence.10 ESGE recommends that, in malignant lesions not amenable to endoscopic excision owing to deep invasion, six carefully targeted biopsies should be taken from the potential focus of cancer.Strong recommendation, low quality of evidence.